2018 IEEE 26th International Requirements Engineering Conference (RE) 2018
DOI: 10.1109/re.2018.00038
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Requirements Negotiation to Sustainability

Abstract: Requirements Engineering (RE) plays a critical role in software system development and is argued to be the key leverage point for practitioners who want to design sustainable software-intensive systems. However, existing RE methods and tools do not explicitly facilitate the discussion and negotiation of sustainability-related concerns. This leads to insufficient or onedimensional perceptions of sustainability. In this paper, we discuss our understanding of sustainability and its relationship with requirements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…A number of studies have attempted to integrate sustainability into specific methods and techniques. Seyff et al, [28] extended the WinWin Negotiation Model to consider the impact of requirements on sustainability. The results of the study suggested that while the approach stimulated the discussion on the multiple dimensions of sustainability, stakeholders found it challenging to identify the impacts of a given requirement on sustainability and were not able to identify the long-term effects.…”
Section: Related Workmentioning
confidence: 99%
“…A number of studies have attempted to integrate sustainability into specific methods and techniques. Seyff et al, [28] extended the WinWin Negotiation Model to consider the impact of requirements on sustainability. The results of the study suggested that while the approach stimulated the discussion on the multiple dimensions of sustainability, stakeholders found it challenging to identify the impacts of a given requirement on sustainability and were not able to identify the long-term effects.…”
Section: Related Workmentioning
confidence: 99%
“…The model component procedure model makes it possible to classify procedure models that cover acquisition and development of software, maintenance of IT systems and user support that also related to directly related, indirectly related and common quality metrics [35].…”
Section: Greensoft Modelmentioning
confidence: 99%
“…The studies provide process models to aid conflict identification and resolution process. Secondly, [13][14][15][16][17] developed tools to improve the performance of requirements negotiation. For example, in [14] the performance of requirements negotiation tools was improved by extending an existing tool with novel concepts of sustainability.…”
Section: Introductionmentioning
confidence: 99%